Association of Lumbar MRI Findings with Current and Future Back Pain in a Population-based Cohort Study. Issue 3 (1st February 2022) - Kasch, Richard; Truthmann, Julia; Hancock, Mark J.; Maher, Christopher G.; Otto, Markus; Nell, Christopher; Reichwein, Niklas; Bülow, Robin; Chenot, Jean-François; Hofer, Andre; Wassilew, Georgi; Schmidt, Carsten Oliver
Abstract : Study Design: Population-based cohort study. Objective: We examined associations between common lumbar degenerative changes observed on magnetic resonance imaging (MRI) and present or future low back pain (LBP). Summary of Background Data: The association between lumbar MRI degenerative findings and LBP is unclear. Longitudinal studies are sparse. Methods: Participants (n = 3369) from a population-based cohort study were imaged at study entry, with LBP status measured at baseline and 6-year follow-up. MRI scans were reported on for the presence of a range of MRI findings. LBP status was measured on a 0 to 10 scale. Regression models were used to estimate the cross-sectional and longitudinal associations between individual and multiple MRI findings and LBP severity. Separate longitudinal analyses were conducted for participants with and without baseline pain. Results: MRI findings were present in persons with and without back pain at baseline. Higher proportions were found in older age groups. 76.4% of participants had a least one MRI finding and 8.3% had five or more different MRI findings. Cross-sectionally, most MRI findings were slightly more common in those with LBP and pain severity was slightly higher in those with MRI findings (ranging from 0.06 for high intensity zone to 0.83 for spondylolisthesis). In the longitudinal analyses, we found most MRI findings were not associated with future LBP-severity regardless of the presence or absence of baseline pain. Compared to zero MRI findings, having multiple MRI findings (five or more) was associated with mildly greater pain-severity at baseline (0.84; 0.50–1.17) and greater increase in pain-severity over 6 years in those pain free at baseline (1.21; 0.04–2.37), but not in those with baseline pain (−0.30; −0.99 to 0.38). Conclusion: Our study shows that the MRI degenerative findings we examined, individually or in combination, do not have clinically important associations with LBP, with almost all effects less than one unit on a 0 to 10 pain scale. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textThe relevance of lumbar magnetic resonance imaging (MRI) findings for future low back pain (LBP) is unclear. Participants from the population-based SHIP study received an MRI examination and reported LBP at baseline and follow-up. Longitudinal associations between MRI findings and LBP were evaluated based on regression models. No clinically important associations were found.